Make an in-depth study into the ways and extents to which the maritime industry may contribute to achieve related UN Global Goals (SDGs) - Nur Darling Imelda Marzuki (Nanyang Technological University, 2021)
Increased cultural, social, and economic issues resulting from unrelenting economic growth have changed our perspective on sustainability. The word "sustainable growth" first appeared in the 1980s, and the idea of sustainability was implicitly framed as an integrated concept later in the 1990s, often referred to as the "triple bottom line" approach. The United Nations (UN) Sustainable Development Goals represent a significant evolution that came to reinforce and define sustainability as an interconnected social, economic, and environmental triptych, among many interventions and attempts to align our economic and societal pursuits with environmental challenges. International shipping, being the world's largest transporter of goods, has a crucial part to play in promoting the UN's sustainability initiative. Despite the abundance of regulatory regulations, codes, and guidelines addressing sustainability in transportation, limited research has been done to determine how well the shipping industry has reacted and contributed to each of the goals individually. Using a qualitative approach, this paper aims to investigate the concept of social sustainability, including what it is, how it influences daily activities, and why it is significant. If social sustainability is not taken into account, it may lead to missed chances or, in the worst-case scenario, unfavourable social consequences. Additionally, the maritime industry’s attitudes and actions towards the social aspects of the sustainable development goals will also be examined to determine what is done well, as well as what is lacking. On top of research data, interviews were done with professionals from the maritime industry. As a result, this paper has also outlined recommendations on how the sustainable development goals can be accomplished in order to enhance social conditions and to ensure the well-being of the future generations.